Kebijakan Formulatif Pencegahan dan Pemberantasan Tindak Pidana Pencucian Uang (Studi Perbandingan Indonesia dan Singapura) - Maulana, Fasya Putri; Elvany, Ayu Izza (Prosiding Seminar Hukum Aktual Fakultas Hukum Universitas Islam Indonesia, 2025)
Abstract This research is motivated by the need for Indonesia to reform the law regarding money laundering crimes that are increasingly developing the types of actions. Currently, Indonesia has enacted Law No. 8 of 2010 on the Prevention and Eradication of the Crime of Money Laundering and most recently regulated in Law No. 1 of 2023 on the Criminal Code. Based on the Mutual Report Evaluation Financial Action Task Force, Singapore is one of the ASEAN countries that has the lowest level of money laundering crime with a strict regulatory structure. So the purpose of this research is to compare regulations between the two countries which hopefully can provide some ideal construction for legal reform in Indonesia. The research method used in this research is normative juridical research by examining secondary data document studies such as legislation and comparative approaches. Based on the research conducted, it is found that there are differences in legal formulations between Indonesia and Singapore, namely related to the broader scope of criminal acts of origin and clarity in several elements of the article so as not to cause various interpretations and there are differences in criminal sanctions for active, passive and corporate actors so as to provide a deterrent effect to perpetrators of money laundering. In addition, the results of this study will provide some forms of ideal construction that can be considered by policy makers to improve regulations related to money laundering in Indonesia.